Analisis Awal Model Inquiry Learning yang dapat Meningkatkan Keterampilan Berpikir Kreatif Mahasiswa - Syamsidah Syamsidah; Ratnawati T.; Amir Muhiddin (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the stages of developing learning tools in the inquiry learning model that can improve students' creative thinking skills, then find out the learning tools of inquiry learning model that are valid, effective, and practical. This research produces learning tools, including Learning Implementation Plan (RPP) with a validated inquiry learning model, a validated module, then a learning mode manual, and a simple IPR (Intellectual Property Right). This research supports the leading research of the State University of Makassar related to the first leading research in the field of education, especially the sub-sector of the Development of Educational Models and Effective Learning. By implementing the inquiry learning model learning tools, students are expected to get multiple benefits, namely: (1) understanding and mastering the material of Kitchen Appliances and (2) increasing students' creative thinking skills. This research is a research on the development of the Thiagarajan, Semmel, and Semmel models which are modified through four stages, namely (1) define stage, (2) design, (3) develop and (4) disseminate. In the develop stage, expert validation is carried out. This research was designed in two stages, the first stage (in 2019) producing an initial prototype design of learning tools. The second stage (2020) aims to develop learning tools for Kitchen Appliance Subjects, testing, evaluation, and revision. The outputs to be achieved in this study are: (1) produce learning tools (lesson plans, modules, and model books) that have been validated by experts, practitioners and have been tested and analyzed, (2) an article will be published in a National proceeding and International journal.